Optimisation algorithms for the charge dispatch of plug-in vehicles based on variable tariffs - Jochen Link; Markus Büttner; David Dallinger; Julius Richter (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2010)
Plug-in vehicles powered by renewable energies are a viable way to reduce local and total emissions and could also support a highly efficient grid operation. Indirect control by variable tariffs is one option to link charging or even discharging time with the grid load and the renewable energy production. Algorithms are required to develop tariffs and evaluate grid impacts of variable tariffs for electric vehicles (BEV) as well as to schedule the charging process optimisation. Therefore a combinatorial optimisation algorithm is developed and an algorithm based on graph search is used and customised. Both algorithms are explained and compared by performance and adequate applications. The developing approach and the correctness of the quick combinatorial algorithm are proved within this paper. For vehicle to grid (V2G) concepts, battery degradation costs have to be considered. Therefore, common life cycle assumptions based on the battery state of charge (SoC) have been used to include degradation costs for different Li-Ion batteries into the graph search algorithm. An application of these optimisation algorithms, like the onboard dispatcher, which is used in the German fleet test "Flottenversuch Elektromobiliät". Grid impact calculations based on the optimisation algorithm are shown.
urn:nbn:de:0011-n-1315659
Keywords: 330; BEV; V2G; Plug-In-Vehicles (PHEV); optimisation; mobile dispatcher; demand side management; charging; combinatorial algorithm; graph search algorithm; indirect control by variable tariffs; Elektrofahrzeug; Tankstelle; Netzwerk; Stromtarif; Mathematische Optimierung; Algorithmus; Theorie